CHANGING PERSPECTIVES IN THE CONCEPT OF "LAGO-MARE" IN MEDITERRANEAN LATE MIOCENE EVOLUTION - Orszag-Sperber F. (My University, 2006)
The Cenozoic Alpine orogeny caused the partition of Tethys into several basins. During the Late Neogene, the Mediterranean attained its final configuration, whereas, eastwards, the Paratethys, isolated from the World Ocean, disintegrated progressively into a series of smaller basins. As a result, an endemic fauna developed in these basins, mainly composed of brackish to freshwater faunas, indicating an environment affected by changes in water salinity. These small basins of the Paratethys were named "Sea-Lakes" by Andrusov [Andrusov, D., 1890. Les Dreissenidae fossiles et actuelles d'Eurasie. Geol. min. 25, 1-683 (in Russian)]. Subsequently this name was translated into "Lac-Mer" [Gignoux, M., 1936. Géologie stratigraphique, 2°édition, Masson, Paris]. In the Mediterranean isolated from the Atlantic at the end of the Miocene (Messinian), thick evaporites deposited, consisting of a marine Lower Evaporite unit and an Upper Evaporite unit, mainly of continental origin. Ruggieri [Ruggieri, G., 1962. La serie marine pliocenica e quaternaria della Val Marecchia. Atti Acad. Sci. Lett. Arti. Palermo, 19, 1-169.] used the term "Lago-Mare", to characterize the brackish to fresh water environment which occurred within the Mediterranean at the end of the Messinian. During recent decades, numerous scientific investigations concerning the history of the Messinian within the Mediterranean were devoted to the understanding of conditions prevailing after the deposition of the marine evaporites. Brackish to freshwater faunas are found in several outcrops and boreholes in the Mediterranean, both in the uppermost beds of gypsum and inter-bedded within the clastic sediments of the Upper Evaporite Unit, immediately preceeding the flooding by the marine Pliocene waters. These faunas, because of their similarities with the fauna described in the Paratethys, were named "Paratethyan", or "Caspi-brackish" fauna, this leading some authors to imply a migration of these fauna from Paratethys to the Mediterranean. However, others refute this hypothesis. New data induced some researchers to consider that exchanges existed between the Mediterranean and the Eastern Paratethys and also between the Mediterranean and the Atlantic Ocean at the Miocene-Pliocene transition. These investigations now take advantage of the accurate time scales established by authors (biostratigraphy, cyclostratigraphy, magnetostratigraphy), allowing good stratigraphic correlations between the Mediterranean and the Paratethys, and precisions on the geodynamic evolution of this area. Furthermore, sediments at the base of the Zanclean (MPl1), locally containing brackish to fresh water faunas conducted authors to attribute this formation to an infra- or pre-Pliocene and also to a Lago-Mare "event". Thus, the "Lago-Mare" concept drifted from its original meaning, and is evolving because of progresses in the understanding of the Mediterranean geodynamics and the adjacent areas during the Miocene-Pliocene transition. © 2006 Elsevier B.V. All rights reserved.
Keywords: BRACKISH ENVIRONMENTS; LAGO-MARE; MEDITERRANEAN; MESSINIAN; NEOGENE; PARATETHYS; Cenozoic::Neogene::Miocene::Messinian; Кайнозой::Неоген::Миоцен::Мессинский